How did the recent increase in the supply of coronary operations in Finland affect socioeconomic and gender equity in their use?. Issue 3 (1st March 2003) - Hetemaa, T; Keskimäki, I; Manderbacka, K; Leyland, A H; Koskinen, S
Abstract : Study objective: To explore how the increased supply of coronary bypass operations and angioplasties from 1988 to 1996 influenced socioeconomic and gender equity in their use. Design: Register based linkage study; information on coronary procedures from the Finnish Hospital Discharge Register in 1988 and 1996 was individually linked to national population censuses in 1970–1995 to obtain patients' socioeconomic data. Data on both hospitalisations and mortality attributable to coronary heart disease obtained from similar linkage schemes were used to approximate the relative need of procedures in socioeconomic groups. Setting: Finland, 2 094 846 inhabitants in 1988 and 2 401 027 in 1996 aged 40 years and older, and Discharge Register data from all Finnish hospitals offering coronary procedures in 1988 and 1996. Main results: The overall rate of coronary revascularisations in Finland increased by about 140% for men and 250% for women from 1988 to 1996. Over the same period, socioeconomic and gender disparities in operation rates diminished, as did the influence of regional supply of procedures on the extent of these differences. However, men, and better off groups in terms of occupation, education, and family income, continued to receive more operations than women and the worse off with the same level of need. Conclusions: Although revascularisations in Finland increased 2.5-fold overall, some socioeconomic and gender inequities persisted in the use of cardiac operations relative to need. To improve equity, a further increase of resources may be needed, and practices taking socioeconomic and gender equity into account should be developed for the referral of coronary heart disease patients to hospital investigations.